Adverse kidney related events following targeted therapies in lung cancer: a systematic review and network meta-analysis of randomized controlled trials - Song Ren; Wei Wang; Xiaoxiu Yao; Wenyan Fang; Guisen Li; Yunlin Feng; Min Xia (Frontiers in Pharmacology)
BackgroundTo summarize current evidence on kidney related adverse events (AEs) following targeted therapies in lung cancer from trial settings.MethodsA systematic search was conducted in MEDLINE, EMBASE, and Cochrane Central Library. Randomized controlled trials that had reported kidney related AEs following targeted therapies in lung cancer were eligible. Outcomes included renal dysfunction as reported, increased serum creatinine, proteinuria, urinary tract infection (UTI), and electrolyte disorders. The risk of bias was assessed using the Cochrane guidelines. The incidence of the examined outcomes, along with their corresponding 95% confidence intervals (CIs), were combined using a random-effects model. Network analysis was applied if the comparisons had passed the consistency test. Publication bias was assessed using Funnel plot analysis.Results57 studies encompassing 11,497 patients were included. The pooled incidences (95% CI) of acute kidney injury (AKI), increased serum creatinine, proteinuria, and UTI following targeted therapies in lung cancer were 1% (0%, 2%), 4% (1%, 8%), 9% (6%, 13%), and 6% (2%, 12%), respectively. Targeted therapies did not increase the risk of AKI, yet were associated with higher incidence of proteinuria, particularly vascular endothelial growth factor inhibitors containing therapies. Multiple electrolyte disorders could be observed following targeted treatments, with the pooled incidences ranging from 4% to 21%; however, most electrolytes disorders had limited number of reports. Most of the reported kidney related AEs were of Common Terminology Criteria for Adverse Events (CTCAE) grade 1 or 2. Publication bias was present for kidney related AEs excluding AKI.ConclusionKidney related adverse events are not uncommon following targeted therapies in lung cancer in trial settings. In comparison to chemotherapy alone, targeted therapies did not increase the risk of AKI, yet were associated with higher risk of proteinuria. Proteinuria and electrolytes disorders are more often observed than renal dysfunction and UTI. All types of AEs were mostly mild in severity.Systematic Review RegistrationPROSPERO CRD42023441979.